The Effect of Workforce Diversity on Employee Performance: The Case of Wallaga University - Gudata Abara Chali; Lema Adeba (Advances in Psychological Sciences and Applications, 2026)
This study investigates the impact of workforce diversity on employee performance at Wallaga University, Ethiopia. Utilizing a descriptive and explanatory research design, the study analyzed four primary dimensions of diversity: ethnicity, gender, education, and age. Quantitative data were gathered from 179 administrative staff members (representing a 93.7% response rate) through structured Likert-scale questionnaires. Data analysis was conducted using SPSS version 24, employing both descriptive statistics and inferential methods, including Pearson correlation and multiple regression. The findings demonstrate that ethnicity, educational background, and age diversity have a statistically significant positive effect on employee performance. Specifically, educational diversity emerged as the strongest predictor of performance (β= 0.422, p < 0.001). While gender diversity showed a positive relationship, its effect was not statistically significant in this specific context (p = 0.636). The regression model explained 68.4% of the variance in employee performance. The study concludes that institutionalizing diversity management is essential for enhancing productivity and recommends that Wallaga University leadership integrate diversity-conscious policies into their strategic human resource frameworks.